PENERAPAN MEDIA PEMBELAJARAN BERBASIS CANVA DALAM POKOK BAHASAN PERUBAHAN MATERI PADA KURIKULUM MERDEKA DI KELAS X SMK ABDURRAB PEKANBARU - Yulia Safitri; Ira Hidayati; Yumna Eltias (Journal of Chemistry Education and Integration, 2023)
AbstractThe importance of learning innovation in the Merdeka Curriculum is to ensure that education can keep up with the times and the needs of students in an era that continues to change. The independent curriculum prioritizes freedom of thought and creativity. The purpose of this study was to determine the application of canva-based learning media in the subject of material changes in the independent curriculum in class X of SMK Abdurrab Pekanbaru. This research method uses qualitative methods. Types of descriptive research. This research was conducted at SMK Abdurrab Pekanbaru. The subjects used are grade X students who have implemented an independent curriculum. The result of this research is that Canva application-based learning media can be applied in the subject of material changes in the independent curriculum. The use of the Canva application can be an effective tool to shape the creativity of SMK Abdurrab Pekanbaru students.Keywords: Canva, Curriculum Merdeka, and Material Change